How aggressive one need to be in treatment of patients with oligometastasis from non-small cell lung cancer? - Noh, Jae Myoung; Ahn, Yong Chan (Journal of Thoracic Disease, 2017)
The concept of “oligometastases” was first proposed by Hellman and Weichselbaum in 1995 and defined as metastases limited in number and location (1,2). Though being in blood-borne nature, eradication of oligometastatic lesions, by aggressive local therapy (surgery and/or radiation therapy), has been shown to provide additional chance for cure to many patients in a few clinical settings.